Watermarking text document based on statistic property of part of speech string - DAI Zu-xu1; HONG Fan1; CUI Guo-hua1; FU Min2 (Tongxin xuebao)
An algorithm resolving nonlinear entropy equation with multivariable was described and proved firstly,then a new scheme where a text document is marked by accommodating probability distribution of certain part of speech strings to entropy constitutes the watermark was designed.Watermark function in the scheme values in a real number set domi-nated by computing precision,it is helpful to advances watermark capacity significantly.